The Human vulnerability as an ethical value in end-of-life care - Radosta, Darío Iván (2021)
In this work we reflect on how the ontologically vulnerable and fragile character of the human can become a useful ethical value to guide the practice of care at the end-of-life. We will address in principle the distinction between contextual and ontological vulnerability, to argue the inherently fragile character of the human condition. We will take the metaphor of the wounded healer as one of the sources from which the idea of ​​vulnerability is introduced as a model of care. Finally, we will present some reflections on how care at the end of life, typical of the hospice philosophy, allows us to think of the scope of human vulnerability as an ethical value constitutive of the practice of caring. Among the proposals, we believe that vulnerability as an ethical value justifies, due to its relationally constructed character, the establishment of symmetrical helping relationships and the need to recognize one's own limits.